Gut Microbiota Signatures in Gestational Anemia - Long, Yan; Liang, Fang; Guo, Ruochun; Zhu, Chunyan; Zhao, Xueqin; Wang, Xifan; Liu, Fei; Jiang, Min; Liang, Qihua; Zeng, Shanshui; Han, Mengru; Qin, Junjie; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Gestational diseases are associated with altered intestinal microbiota in pregnant women. Characterizing the gut microbiota of gestational anemia (GA) may describe a novel role of gut microbial abnormality in GA. In this study, we investigated differences in gut microbiota between GA patients and healthy pregnant women from the first trimester (n = 24 vs. 54) and the third trimester (n = 30 vs. 56) based on the 16S rRNA gene sequencing method. No statistically significant differences in α-diversity were identified between GA patients and controls in the first trimester of pregnancy, whereas the Shannon index and observed OTUs were significantly lower in GA patients than in healthy controls in the third trimester. Distance-based redundancy analysis revealed striking differences in microbial communities in the third trimester between GA patients and controls. Four genera were significantly different in relative abundance between GA patients and healthy controls, while 12 genera differentiated significantly between GA patients and healthy controls in the third trimester. At the operational taxonomic unit (OTU) level, 17 OTUs and 30 OTUs were identified to be different between GA patients and healthy controls in the first and third trimesters, respectively. Changes in gut microbial composition of GA patients suggest a potential relation with GA and provide insights into the prediction and intervention of gestational anemia.